KLASIFIKASI KARAKTER BERDASARKAN PENILAIAN SIKAP SOSIAL TEMAN SEJAWAT PADA KURIKULUM 2013 MEMANFAATKAN NAIVE BAYES - Imron Rosadi (Universitas Islam Lamongan, 2018)
This aim of this researh is to classify an assessment sentence from students, then classified to produce an information. Classification is used to determine the character of each student so that teachers have no difficulty in assessing the social character of the student, based on asesment orientation On Kurikulum 2013. This research is empasize to processing opinion for the students to evaluate their friend in SMA Negeri 1 Ngimbang Lamongan, and the opinion to evaluate each student will classified into 6 social attitudes that is Honest, Discipline, Responsibility, Pay Attention (mutual cooperation, tolerance), well manered and selsf confidence, this research is divide into 2 phase that is the process to produce training data (dataset) and the process to classify opinion (test data). Both off the process are to at extracting the attributes and object components which commented in every document and to decide the classification social attitudes classfication for each student.On the system for this character clasification produce accuracy with the sucess rate from the result of the testing clasficataion use Algoritman Naive Bayes success rate of 72%, this approach paper I use of 80%, the succes rate of 72% because the use of the sentence for rating colleague had the rate of variants are quite low that affect the process off making the data that will be used to the system off the clasificaton of characterer